The Role of Sharia Bank Green Financing in Improving the Sustainability Performance of MSMEs - Pungky Lela Saputri; Hanif Ahmadi (www.amertainstitute.com, 2026)
This study investigates the role of Islamic bank green financing in enhancing the sustainability performance of micro, small, and medium enterprises (MSMEs) by integrating external and internal determinants. Specifically, it examines the effects of access to Islamic green financing, Islamic green financial literacy, and environmental commitment on the sustainability performance of culinary MSMEs in Semarang City, Indonesia. Employing a quantitative explanatory research design, primary data were collected from 150 MSMEs selected using the Slovin formula from a population of 240 enterprises. Data were gathered through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression. The empirical findings reveal that access to Islamic green financing, Islamic green financial literacy, and environmental commitment each have a positive and statistically significant effect on MSMEs’ sustainability performance, both individually and simultaneously. Among these factors, Islamic green financial literacy emerges as the most dominant determinant, indicating that knowledge and understanding of Sharia-compliant green finance play a critical role in translating financial access into sustainable business practices. The results suggest that the effectiveness of Islamic green financing is not solely dependent on the availability of funds, but also on MSMEs’ financial capabilities and commitment to environmental responsibility. This study contributes to the literature on sustainable Islamic finance by providing empirical evidence from the MSME sector in a developing economy context. Practically, the findings offer insights for Islamic banks and policymakers in designing more inclusive green financing schemes accompanied by financial literacy and environmental capacity-building programs to support sustainable MSME development.